Review: The Book of Esther in Modern Research - Tollington, Janet E. (The journal of theological studies, 2004)
The Book of Esther in Modern Research Sidnie White Crawford Leonard J. Greenspoon Pp. xii+266 (Journal for the Study of the Old Testament Supplement Series, 380.)London T. & T. Clark International (A Continuum Imprint) 2003 0 8264 6663 X £70